27 Has the time come for offering day-case atrial fibrillation ablation? patient and procedural characteristics indicative of early uptake. (June 2018) - Bartoletti, Stefano; Mann, Mandeep; Gupta, Akanksha; Khan, Abdul; Sahni, Ankita; El-Kadri, Moutaz; Hobbs, Julian; Modi, Simon; Waktare, Johan; Mahida, Saagar; Hall, Mark; Snowdon, Richard; et al.
Abstract : Background: Catheter ablation for atrial fibrillation (AF) has traditionally involved at least an overnight stay in hospital. We hypothesised that systematic use of ultrasound-guided venous access and implementation of streamlined peri-ablation anticoagulation policy would allow early mobilisation for patients and facilitate same-day discharge. Methods: From 2014 we started offering same-day discharge to selected patients who underwent uncomplicated AF ablation on the morning lists (procedure end before 14:00 hours), with no routine post-ablation echocardiogram. Patients were discharged between 19:00 and 20:00. hours and offered access to a dedicated heart rhythm nurse helpline. Our AF ablation policy includes mandatory use of vascular ultrasound for femoral access, uninterrupted warfarin pre-procedure, minimal interruption in non-vitamin K oral anticoagulants (omitted only on the morning of the procedure), avoidance of bridging with low molecular weight heparin and reversal of intraprocedural heparin with protamine before femoral sheath removal. Results: Over a 3 year period from April 2014 to March 2017 we performed 811 AF ablation cases on the morning lists, of which 169 (20.8%) were discharged on the same day (52 females, mean age 59±11, mean BMI 29±5 kg/m 2, mean CHA2 DS2 -VASc 1±1). One patient (0.6%) had a procedural complication (transient right phrenic nerve palsy which resolved before discharge), while 5 (2.9%) cases experienced minor problems which did not preclude same-day discharge (2 with hypotension, 1 minor femoral bleeding, 1 sore throat post-intubation, 1 nausea and vomiting). Post-discharge, 4 (2.3%) patients needed readmission for minor problems (2 for pericarditic chest pain and 2 for nausea/vomiting). Compared to the 642 cases from the morning lists who stayed overnight, day-case procedures were significantly shorter in duration and in energy delivery time, more likely to be redos, less likely to include electrical cardioversion and more likely to be performed under sedation rather than general anaesthesia. There were no significant differences in patient age (59±11 vs 59±11, p=0.98) or gender (52/169 versus 205/642 females, p=0.77), in pre-procedural anticoagulation regimen (warfarin versus non-vitamin K anticoagulants versus no anticoagulation) and in choice of ablation Method (cryoballoon versus radiofrequency) [see table 1]. Conclusion: A streamlined protocol, including ultrasound-guided venous access, allows for safe day-case AF ablation. Its wider adoption can potentially reduce health-care costs while improving patient experience.